Rapid divergence of mussel populations despite incomplete barriers to dispersal - Diede L. Maas; Stefan Prost; Ke Bi; Lydia L. Smith; Ellie E. Armstrong; Ludi P. Aji; Abdul Hamid A. Toha; Rosemary G. Gillespie; Leontine E. Becking (Molecular Ecology, 2018)
Striking genetic structure among marine populations at small spatial scales is becoming evident with extensive molecular studies. Such observations suggest isolation at small scales may play an important role in forming patterns of genetic diversity within species. Isolation‐by‐distance, isolation‐by‐environment and historical priority effects are umbrella terms for a suite of processes that underlie genetic structure, but their relative importance at different spatial and temporal scales remains elusive. Here, we use marine lakes in Indonesia to assess genetic structure and assess the relative roles of the processes in shaping genetic differentiation in populations of a bivalve mussel ( Brachidontes sp.). Marine lakes are landlocked waterbodies of similar age (6,000–10,000 years), but with heterogeneous environments and varying degrees of connection to the sea. Using a population genomic approach (double‐digest restriction‐site‐associated DNA sequencing), we show strong genetic structuring across populations (range F ST : 0.07–0.24) and find limited gene flow through admixture plots. At large spatial scales (>1,400 km), a clear isolation‐by‐distance pattern was detected. At smaller spatial scales (

Time transfer using GPS carrier phase: error propagation and results - R. Dach; G. Beutler; U. Hugentobler; S. Schaer; T. Schildknecht; T. Springer; G. Dudle; L. Prost (Journal of Geodesy, 2003)

Acting on actin: the electric motility assay - Daniel Riveline; A. Ott; Frank Jülicher; Donald A. Winkelmann; Olivier Cardoso; Jean-Jacques Lacapère; Soffia Magnúsdóttir; J. L. Viovy; Laurence Gorre-Talini; Jacques Prost (European Biophysics Journal, 1998)

Axial and transverse stiffness measures of cochlear outer hair cells suggest a common mechanical basis - M. Ulfendahl; Eliza Chan; William B. McConnaughey; Scott Prost-Domasky; Elliot L. Elson (Pflügers Archiv - European Journal of Physiology, 1998)